Prevalence of Cardiovascular Disease Risk Factors in the Women Population Covered by Health Centers in Ardabil - Leli Avesta; Sina Rasoolzadeh; Mahdi Naeim; Aziz Kamran (International Journal of Hypertension)
Objective. This study aimed to determine the prevalence of cardiovascular risk factors in the population of women aged 30 to 60 years covered by health centers in Ardabil. Methods. This retrospective descriptive-analytical study was conducted on 1006 women aged 30 to 60 years who were covered by Ardabil comprehensive urban health service centers, and they were selected by using the multistage random sampling method. In the first stage, health centers in Ardabil were divided into five geographical areas, and the population covered by each of the five areas was calculated. In the second stage, the number of samples was allocated as a quota in the regions, and in the third stage, in proportion to the population covered by each center in Ardabil, the samples were selected. Women with one of the conditions of pregnancy, lactation, history of kidney disease, known diabetes under medication, history of hepatitis, history of cardiovascular surgery, and history of cancer were excluded from the research process. Results. The average activity of individuals was 24.42 minutes per day. The mean intake of fruits and vegetables was 1.9 ± 0.9 and 2.1 ± 1.07 unit/day, respectively, and meat was 286.6 ± 174.6 grams per week. The mean of HDL, LDL, TG, cholesterol, and FBS were 43.6 ± 10.4, 101.28 ± 26.3, 159.89 ± 54.01, 185.99 ± 37.9, and 94.62 ± 13.3 mg/dl, respectively. The mean systolic blood pressure (SBP) and diastolic blood pressure (DBP) were 108.14 and 68.26 mmHg, respectively. Conclusions. Abdominal obesity (waist above 88), obesity and overweight (high body mass index), high triglycerides, high cholesterol, and LDL and HDL outside the proper range were the most important and risk factors for cardiovascular disease among women.